2023
DOI: 10.1093/jme/tjad095
|View full text |Cite
|
Sign up to set email alerts
|

The known unknowns of Powassan virus ecology

Doug E Brackney,
Chantal B F Vogels

Abstract: Powassan virus (POWV; Family: Flaviviridae, Genus: Flavivirus) is the sole North American member of the tick-borne encephalitis sero-complex. While associated with high rates of morbidity and mortality, POWV has historically been of little public health concern due to low incidence rates. However, over the last 20 yr, incidence rates have increased highlighting the growing epidemiological threat. Currently, there are no vaccines or therapeutics with tick habitat reduction, acaricide application, and public awa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…The mechanisms behind the focality of DTV transmission cycles in Massachusetts and the surrounding northeast states remain poorly understood [ 16 ]. The variation in site-specific infection prevalence (0–10.4%) on a relatively small scale observed in our survey of host-seeking ticks may be partially attributed to the limited sampling power and scale inherent in active surveillance efforts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms behind the focality of DTV transmission cycles in Massachusetts and the surrounding northeast states remain poorly understood [ 16 ]. The variation in site-specific infection prevalence (0–10.4%) on a relatively small scale observed in our survey of host-seeking ticks may be partially attributed to the limited sampling power and scale inherent in active surveillance efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Shrews ( Sorex spp. ; Blarina brevicauda ) have recently been implicated as reservoir hosts for DTV, and many unknowns still exist around DTV ecological maintenance and amplification [ 15 , 16 ]. Deer Tick Virus is considered a greater public health threat due to the opportunistic nature of I. scapularis [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recent laboratory studies demonstrate that D. variabilis , H. longicornis and Amblyomma americanum are competent vectors for POWV II [ 23 , 24 ]. These findings suggest that the transmission cycles of POWV I and POWV II could be more complex than the single tick vector species/single reservoir host paradigm [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prior to this work by Jones et al., it was believed that an obvious viremia and systemic infection was necessary for ticks to acquire virus during blood feeding; however, Jones’ work was paradigm shifting in that it demonstrated that tick-to-tick transmission of virus can occur via nonviremic hosts. To date, no reservoir host has been clearly defined for POWV II; therefore, it is possible that POWV II may be sustained in natural transmission cycles via nonviremic transmission between co-feeding ticks [ 39 ], as has been shown for tick-borne encephalitis virus (TBEV) transmission in Europe [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple phylogeographic analyses of POWV genomes suggest that the virus exists in discrete transmission foci with infrequent dispersal between enzootic sites [ 15 , 16 ]. Such isolation could imply adaptation to local transmission conditions such as host or vector diversity and genetic background, as well as extrinsic influences such as microclimate [ 17 ]. Indeed, geographic risk of human POWV disease appears to be heterogeneous, with Massachusetts, Wisconsin, Minnesota, Maine, and New York accounting for >90% of all cases [ 5 ].…”
Section: Introductionmentioning
confidence: 99%